Treaty-Curses and the Old Testament Prophets - Hillers, Delbert R. (1964)
spez. I. The Problem and the Sources; II. Types of Treaty-Curse and Their History; IV. Old Testament Parallels to Treaty-Curses (keilschriftlicher Staatsverträge).